Effect Of Feeding Formaldehyde Treated Groundnut Cake On Growth Performance Of Barbari Kids - Singh, V.P.; Nayak, S.; Baghel, R.P.S.; Gupta, R.S.; Patil , A.K.; Khare , A. (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
An experiment was conducted on 14 barbari goat kids to evaluate the effect of protected ground nut cake (GNC) on performance of growing kids for 90 days. In treatment T1 (control) kids were given untreated GNC on growth performance Significant (P<0.05) higher body weight and average daily weight gain were recorded with kids fed on protected GNC based ration as compared to kids that were not fed bypass protein based ration (control group). Dry matter intake (DMI) of kids was not affected by feeding bypass protein based ration. Feed efficiency ratio (FER) was better (P<0.05) in kids fed on formaldehyde treated GNC based ration (0.17±0.00) then untreated GNC based ration (0.15±0.00